Inherited Fibrinolytic Disorder Due to an Enhanced Plasminogen Activator Level - Aznar, J; Estellés, A; Vila, V; Regañón, E; España, F; Villa, P (Thrombosis and Haemostasis, 1984)
A family with “in vitro” increased red-cell fall out from the blood clot was studied. One member of the family (JVM) had a clinical history of hemorrhages after minor trauma or dental extractions. Routine coagulation and platelet function were normal except for the fibrinogen level which was slightly low in several members. The antigenic as well as functional evaluation of factor XIII was within normal limits. No factor XIII inhibitors were present. An increase in the clot permeability index was observed in most family members.The study of the fibrinolytic system showed an enhanced lysis of euglobulins, a normal plasminogen value, normal level of fibrin/ogen degradation products, normal fibrinolytic inhibitors, and an increase in the activity of the plasminogen activator. The activity of this activator was inhibited by an antiserum against tissue-type plasminogen activator. The t-pA inhibitor was in the normal range.It is concluded that the family studied in this paper shows familial alteration in the fibrinolytic system due to an excess of plasminogen activator immunologically related to that in human tissue.
Keywords: Fibrinolytic hyperactivity; Tissue-type plasminogen activator; Familial hyperfibrinolysis